Three new species of Pomphopsilla Jałoszyński in Togo (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
The cephenniine genus Pomphopsilla currently comprises twelve nominal species distributed in Burundi, DR Congo, Kenya, Rwanda and the Seychelles. Three new species are described, all based on specimens collected in Togo: P. spinosa sp. n., P. bifurcata sp. n. and P. klotoensis sp. n. The distribution of Pomphopsilla is summarized.